2008
DOI: 10.1590/s1516-44462008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Revisão: funcionamento executivo e uso de maconha

Abstract: Revisão: funcionamento executivo e uso de maconha Review: executive functioning and cannabis use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
0
16
0
5
Order By: Relevance
“…Executive functioning (EF) plays a role in the development and maintenance of substance use disorders (SUD; Almeida et al, 2008). EF includes processes such as planning, organization, decision-making, set shifting and maintenance, working memory, and the like (Lezak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Executive functioning (EF) plays a role in the development and maintenance of substance use disorders (SUD; Almeida et al, 2008). EF includes processes such as planning, organization, decision-making, set shifting and maintenance, working memory, and the like (Lezak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is broad consensus that cannabis intoxication often results in short-term dysfunction across a range of cognitive domains in healthy volunteers (Makela et al, 2006; Almeida et al, 2008; Hunault et al, 2009), though not all studies have been consistent in this regard (Heishman et al, 1997; Almeida et al, 2008; Hart et al, 2010). The extent to which chronic cannabis use is also associated with cognitive impairments remains less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Early cross-sectional studies reported associations between heavy chronic cannabis use and impaired verbal fluency and word recognition memory; some studies reported that these deficits persisted for just a few days following cessation of cannabis intake (Pope et al, 2001), while others suggested that these deficits persisted for a month or longer (Bolla et al, 2002; Pope et al, 2003). Research using various neuropsychological tests has confirmed that chronic cannabis use can be associated with dysfunction across a range of functions including aspects of memory, attention, inhibitory control, and executive planning (Almeida et al, 2008; Solowij and Pesa, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The executive processing is related to the human ability to obtain information by different brain systems, verbal or nonverbal, and act to produce new responses 14 . Working memory and inhibitory control are two cognitive processes that underlie the executive function.…”
mentioning
confidence: 99%
“…Working memory and inhibitory control are two cognitive processes that underlie the executive function. The first, refers to the ability to maintain and manipulate information in short-term to generate an action in the near future; and the latter, refers to a process that aims to suppress internal or external influences that might interfere with ongoing behavioral sequence 14 . Losses in the executive control system of working memory may explain some of the cognitive and behavioral problems displayed by individuals who use multiple drugs, identified as more impulsive than the control group 15 .…”
mentioning
confidence: 99%